Orderings of higher level in multifields and multirings - Gładki, Paweł (Annales Mathematicae Silesianae, 2010)
In this note we generalize the concept of orderings of higher level to multifields and multirings. We show how part of the standard Artin-Schreier theory for orderings of higher level of fields and rings extends to multifields and multirings.